Cues from human atrial extracellular matrix enrich the atrial differentiation of human induced pluripotent stem cell-derived cardiomyocytes. (16th April 2021) - Mesquita, Fernanda C. P.; Morrissey, Jacquelynn; Lee, Po-Feng; Monnerat, Gustavo; Xi, Yutao; Andersson, Helen; Nogueira, Fabio C. S.; Domont, Gilberto B.; Sampaio, Luiz C.; Hochman-Mendez, Camila; Taylor, Doris A.
Abstract : Decellularized extracellular matrix (dECM) from human atria preserves key native components that directed the cardiac differentiation of hiPSCs to an atrial-like phenotype, yielding a twofold increase of functional atrial-like cells. Abstract : New robust and reproducible differentiation approaches are needed to generate induced pluripotent stem cell (iPSC)-derived cardiomyocytes of specific subtypes in predictable quantities for tissue-specific disease modeling, tissue engineering, and eventual clinical translation. Here, we assessed whether powdered decellularized extracellular matrix (dECM) particles contained chamber-specific cues that could direct the cardiac differentiation of human iPSCs toward an atrial phenotype. Human hearts were dissected and the left ventricle (LV) and left atria (LA) were isolated, minced, and decellularized using an adapted submersion decellularization technique to generate chamber-specific powdered dECM. Comparative proteomic analyses showed chamber-specific dECM segregation, with atrial- and ventricle-specific proteins uniquely present in powdered dECM-hA and dECM-hV, respectively. Cell populations differentiated in the presence of dECM-hA showed upregulated atrial molecular markers and a two-fold increase in the number of atrial-like cells as compared with cells differentiated with dECM-hV or no dECM (control). Finally, electrophysiological data showed an increase in action potentials characteristic of atrial-like cells in the dECM-hA group. These findings support the hypothesis that dECM powder derived from human atria retained endogenous cues to drive cardiac differentiation toward an atrial fate.